Bioproduction of Chitin Hydrolysate Containing N-Acetylglucosamine by Serratia marcescens PT6 Crude Chitinase and Its Effects on Bacterial Growth Inhibition in Various Temperature - Indun Dewi Puspita; Susana Endah Ratnawati; Hendri Setiawan; Murwantoko Murwantoko; Ustadi Ustadi; David Ratkowsky; Mark Tamplin (ASEAN Journal of Chemical Engineering, 2023)
N-acetylglucosamine (GlcNAc), a chitin monomer, can be used as a natural preservative to ensure food quality and safety. Combining natural preservatives with low storage temperature offers physical hurdles to bacterial growth in food. This study aimed to produce chitin hydrolysate containing GlcNAc using Serratia marcescens PT6 crude chitinase and investigate its effect on bacterial growth rate as a function of temperature. Crude chitinase from partial purification was used to hydrolyze 1.3% colloidal chitin. The optimal enzymatic conditions were pH 6 and 45˚C for 120 min, at an enzyme:substrate ratio of 1:1, yielding a 65.6 µg/mL GlcNAc. Inhibitory activity of hydrolysate containing 2.5-7.5 ppm GlcNAc on Escherichia coli, Staphylococcus aureus, Bacillus cereus, and Vibrio parahaemolyticus was measured at 4, 15, and 30oC in nutrient broth. Bacterial growth was measured using of optical density for each combination of GlcNAc concentration and temperature. Growth curves fitted by the Baranyi and Roberts model were developed using DMFit software. The growth rate was converted to the square root and then modeled as a function of temperature using the Ratkowsky square root model. Incubation temperature exerted a pronounced effect on the inhibition of all bacterial species (P<0.0001), with the greatest effect observed for E. coli at 30°C (P<0.0001), and the least effect for V. parahaemolyticus (P=0.0878). The inhibitory effect of GlcNAc in chitin hydrolysate was only significant for E. coli (P<0.0001) and S. aureus (P=0.0041). This study revealed that the effect of temperature in growth inhibition was more significant than GlcNAc addition. However, a reduction in bacterial growth with the addition of GlcNAc at 30°C was observed, which may be effective for food encountered thermal abuse conditions. Further investigation of the effect of GlcNAc on bacteria structure and metabolism is required to elucidate the mechanism of GlcNAc as a food preservative.